Lectures of the School of Advanced Training on the Pediatric Microbiota [Scuola di Alta Formazione sul Microbiota in Età Pediatrica]; webinar; February-March 2022 - - (Hygeia Press di Corridori Marinella, 2022)
Lectures of the School of Advanced Training on the Pediatric Microbiota [Scuola di Alta Formazione sul Microbiota in Età Pediatrica] An all-around view of the microbiota for clinical pediatric practice [Il microbiota a 360 gradi per la pratica clinica pediatrica] Webinar • February-March 2022   The meeting has been organized with the unconditional contribution of BROMATECH.   LECT 1. THE SCHOOL OF ADVANCED TRAINING ON THE PEDIATRIC MICROBIOTA [LA SCUOLA DI ALTA FORMAZIONE SUL MICROBIOTA IN ETÀ PEDIATRICA] • V. Fanos, M. Romeo (Cagliari and Pavia, Italy)  LECT 2. YOU WILL NEVER FORGET YOUR FIRST MICROBIOTA [IL PRIMO MICROBIOTA NON SI SCORDA MAI] • V. Fanos (Cagliari, Italy) LECT 3. BREASTFEEDING, WEANING AND HEALTHY GROWTH OF THE BABY [ALLATTAMENTO, SVEZZAMENTO E CRESCITA SANA DEL BAMBINO] • D.G. Peroni (Pisa, Italy) LECT 4. THE ROLE OF GUT MICROBIOTA AND PROBIOTICS SUPPLEMENTATION IN THE MANAGEMENT OF INFANTILE COLIC [IL RUOLO DEL MICROBIOTA INTESTINALE E DELL'INTEGRAZIONE PROBIOTICA NELLA GESTIONE DELLE COLICHE INFANTILI] • M. Romeo (Pavia, Italy) LECT 5. A JOURNEY INTO THE MICROBIOTA AMONG ALLERGIES AND IMMUNE SYSTEM DISEASES [VIAGGIO NEL MICROBIOTA TRA ALLERGIE E MALATTIE DEL SISTEMA IMMUNITARIO] • R. Castagnoli, G.L. Marseglia (Pavia, Italy) LECT 6. WHAT IS EVIDENT IN METABOLIC DISORDERS: OBESITY, DIABETES AND MICROBIOTA [EVIDENZE NEI DISORDINI METABOLICI: OBESITÀ, DIABETE E MICROBIOTA] • G. Banderali (Milan, Italy) LECT 7. THE KNOWLEDGE OF THE MICROBIOTA IN PRIMARY CARE [I RISVOLTI PRATICI DELLE CONOSCENZE SUL MICROBIOTA] • G. Trapani, G. Maiocco, A. Spadavecchia (Sanremo and Turin, Italy) LECT 8. MICROBIOTA AND NUTRITION IN PEDIATRIC AGE [MICROBIOTA E NUTRIZIONE IN ETÀ PEDIATRICA] • L. Emma (Turin, Italy) LECT 9. THE MUCO-MICROBIOTIC LAYER: THE INNERMOST COMPONENT OF THE BOWEL WALL [LO STRATO MUCO-MICROBIOTICO: LA COMPONENTE PIÙ INTERNA DELLA PARETE INTESTINALE] • F. Cappello (Palermo, Italy) LECT 10. PROBIOTICS ARE NOT ALL THE SAME [I PROBIOTICI NON SONO TUTTI UGUALI] • R. Francavilla, F. Cristofori (Bari, Italy) LECT 11. IS THERE A MICROBIOME SIGNATURE IN PEDIATRIC INFLAMMATORY BOWEL DISEASE? [VI È UN MICROBIOMA INTESTINALE SPECIFICO NELLE MALATTIE INFIAMMATORIE CRONICHE INTESTINALI PEDIATRICHE?] • M. Martinelli, A. Staiano (Naples, Italy) LECT 12. MICROBIOTA AND NEURODEVELOPMENT [MICROBIOTA E NEUROSVILUPPO] • P. Rossi (Pavia, Itay) LECT 13. MICROBIOMICS AND METABOLOMICS IN AUTISM SPECTRUM DISORDER [MICROBIOMICA, METABOLOMICA E DISTURBI DELLO SPETTRO AUTISTICO] • M. Mussap (Cagliari, Italy) LECT 14. WHAT FUTURE FOR HUMAN HEALTH? [QUALE FUTURO PER LA SALUTE UMANA?] • A. Maglioni (Civitella di Romagna, Italy)